Comparing the Plot of the Maze Runner ( 2014 ) and the story of Ashabul Kahfi : An Analysis using Narrative theory - Nurul Fidya Harya (Fak. Adab dan Ilmu Budaya Universitas Islam Negeri, 2023)
et,1/Mumtaz c.1